Short-term effects of biochar on soil properties and wheat yield formation with meat bone meal and inorganic fertiliser on a boreal loamy sand - Tammeorg, Priit; Simojoki, Asko; Mäkelä, Pirjo; Stoddard, Frederick L.; Alakukku, Laura; Helenius, Juha (Agriculture, ecosystems & environment, 2014)
•Biochar effects on soil properties and yield formation of wheat were studied.•5 levels of biochar were applied with or without inorganic fertiliser or meat bone meal.•After an initial decrease, biochar increased the NO3−-N content of the soil in year 2.•Biochar addition improved soil WRC, SOC and K content but not crop performance.•Biochar effects did not differ between the fertiliser types. Poor water retention capacity (WRC) and nutrient deficiency commonly limit crop yields in sandy soils. The use of biochar as a soil amendment has been previously reported to improve these limiting factors in subtropical and temperate soils. We studied the effects of biochar on soil properties and yield formation of spring wheat (Triticum aestivum L.) when applied together with inorganic fertiliser or meat bone meal (MBM) to an Endogleyic Umbrisol with a loamy sand texture in boreal conditions. In a two-year field experiment, biochar was applied at 0, 5, 10, 20 and 30tha−1 combined with three fertiliser treatments (unfertilised control, MBM and inorganic fertiliser) providing equal amounts of nitrogen (N), phosphorus (P) and potassium (K). Soil WRC and fertility as well as wheat yield, yield components and quality were analysed. Soil moisture content, leaf area index and leaf chlorophyll values (SPAD) were monitored during the experiment. Biochar increased the plant-available water content of the topsoil in the first year and reduced the bulk density in the second year after application. It also increased the contents of easily soluble K and soil organic C (SOC) in the 20cm of topsoil, but had no effects on other soil nutrients, pH or moisture content. Biochar amendment decreased the soil NO3−-N content below control values in the first year but increased it significantly in the second year. The addition of biochar did not significantly affect the nitrogen uptake, grain yield or quality of wheat, possibly because of its low nutrient availability and the high organic matter content of the soil.